12-month outcomes of GLP - 1 in severe pediatric obesity: real-world data - Cominato, Louise; Resende, Mariana L.; Bernardes, Natalia; Rachid, Ludmila L.; Passone, Caroline G. B.; Mattar, Larissa B. F.; Neme, Georgia; Souza, Sarah G.; Santos, Claudia Renata P.; Franco, Ruth R.; Damiani, Durval (Frontiers in Endocrinology, 2025)
BackgroundReal-world data on liraglutide for pediatric obesity is limited, especially in public healthcare systems of low- and middle-income countries.ObjectiveTo evaluate the real-world effectiveness and safety of liraglutide in managing severe obesity among children and adolescents with severe obesity treated at a public quaternary hospital in Brazil.MethodsThis cohort study included patients aged 6–17.9 years with BMI Z-score (Z-BMI) ≥+3, treated with liraglutide (up to 3.0 mg/day) and lifestyle intervention. Outcomes included changes in BMI, Z-BMI, weight, WHtR, metabolic markers, and adverse events over 3 months, 6 months and 12 months.ResultsOf 74 patients, 55 completed 6 months and 22 completed 12 months. In patients aged 6–12 years (n=23), median Z-BMI decreased from +3.90 (3.4 - 5.1) to +3.06 (2.7 - 3.7) (p < 0.0001), and WHtR from 0.70 (0.66 - 0.73) to 0.64 (0.60 - 0.68) (p < 0.0001); 82.6% achieved ≥5% BMI reduction and 47.8% ≥10% BMI reduction. In adolescents aged ≥12 years (n=32), Z-BMI declined from +3.77 (3.02 - 4.66) to +3.48 (2.64 - 4.34) (p < 0.0001), and WHtR from 0.74 (0.62 - 0.80) to 0.67 (0.58 - 0.76) (p < 0.0001); 73.9% achieved ≥5% and 43.5% ≥10% BMI reduction. Improvements were also observed in LDL cholesterol, HbA1c, and HOMA-IR. Adverse events were mild and transient.ConclusionLiraglutide was effective and safe in reducing adiposity and improving metabolic health in children and adolescents with severe obesity in a real-world setting.